ANALISIS KADAR FORMALIN DIKAITKAN DENGAN JUMLAH KOLONI BAKTERI PADA IKAN CAKALANG (Katsuwonuspelamis) DAN TAHU YANG BEREDAR DI PASAR-PASAR TRADISIONAL DI KOTA MANADO - Oessoe, Yoakhim Y.; Ngantung, Imelda (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2019)
AbstractFormalin is not a food preservation but is still often found in food product. This situation encourages research with purpose to identify and determine the formalin levels on skipjack fish and tofu from traditional markets in Manado and calculate the number of bacterial colonies in that food product.This research uses purposive sampling method and continued with laboratory test. The results showed that skipjack fish was containing formalin in the location of Karombasan and Bahu market whereas at Bersehati market was not detected. Tofu which was circulating in some traditional markets in Manado, did not contain of formalin. The average formalin levels of skijack fish sold in the Karombasan market were 3.27 ppm while average formalin levels in skipjack fish at the Bahu market were 2.16 ppm. The results of Total plate Count ( TPC) test on skipjack fish showed that in the fish containing high formalin level had low TPC detected bacterial value, on the other hand the fish with low formalin levels obtained high TPC bacterial values. The bacterial TPC value in skipjack and tofu had exceeded the maximum permitted limit.Â Keywords: Skipjack fish, tofu, formalinÂ  conten, Total Plate Count (TPC)